Analysis of Students' Ability to Read the Qur'an Based on Their Learning Environment Support - Muhammad Rizqi; Zainap Hartati; Abdullah (Jurnal Komunikasi Pendidikan, 2025)
This study aims to analyze the ability of students at SMPN 7 Cempaga to read the Qur'an. Using a descriptive qualitative approach, data was collected through observation, in-depth interviews, and documentation of 10 seventh-grade students, Islamic Education teachers, the Deputy Head of Student Affairs, and the Principal. The results of the study indicate that the absence of a program to encourage Quran reading at school, limited time for religious education, and a lack of support and guidance from parents are the main factors contributing to the students' low ability to read the Quran. Additionally, limited facilities such as the availability of Quran manuscripts at home and an unsupportive social environment further exacerbate the situation. These findings emphasize the need for collaboration between schools, families, and the community in fostering sustainable Quran reading habits, through the implementation of special programs at school, enhancing parental involvement, and providing adequate learning facilities. With collective efforts, it is hoped that students' Quran reading skills will develop optimally and support character development and the quality of religious education at SMPN 7 Cempaga.